(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Many alternative energy sources can be used instead of fossil fuels. The decision as to what type of energy source shoud be utilized in each case must be made based on economic, environmental, and safety considerations. Because of the desired environmental and safety aspects it is widely believed that solar energy should be utilized instead of other alternative energy forms it can be used sustainably without harming the environment. The paper deals with the solar photovoltaic module capacity recording device whose load characteristic is similar battery charging load characteristic. As a result, the device will record the amount of energy retrieved from the module battery. In 2009th with this device was recorded solar module PVM10/12PF power and charged batteries are retrieved energy levels in the months and year as a whole.